Association of Maternal Creatinine-to-Body Weight and Urea-to-Creatinine Ratios with Gestational Diabetes Mellitus - Ayas Özkan, Merve; Dayanan, Ruken; Duygulu Bulan, Dilara; Özkan, Halis Doğukan; Aktemur, Gizem; Karabay, Gülşan; Tokgöz Çakır, Betül; Şeyhanlı, Zeynep; Atılgan Yıldırım, Ayşegül; Akın, Furkan; Vural Yılmaz, Zehra (The European Research Journal, 2026)
Objectives: Gestational diabetes mellitus (GDM) is a multifactorial metabolic disorder associated with altered glucose metabolism and systemic physiological adaptations during pregnancy. Subtle changes in renal-related biochemical parameters may reflect underlying metabolic alterations accompanying GDM. This study aimed to evaluate the association between maternal creatinine-to-body weight (Cre/BW) and urea-to-creatinine (Urea/Cre) ratios and GDM, with a particular focus on their potential role as renal–metabolic indicators during pregnancy. Methods: This retrospective case–control study included 1,064 pregnant women (532 with GDM and 532 matched controls) who underwent a 75 g oral glucose tolerance test between 24 and 28 weeks of gestation. Propensity score matching was applied to reduce baseline differences between groups. Maternal serum creatinine, urea, and body weight were recorded in the first and second trimesters, and Cre/BW and Urea/Cre ratios were calculated. Group comparisons, receiver operating characteristic (ROC) analyses, and multivariate logistic regression were performed. Results: In the second trimester, the Cre/BW ratio was significantly lower, and the Urea/Cre ratio was significantly higher in women with GDM compared with controls (both P<0.001). The Cre/BW ratio demonstrated moderate discriminatory ability for distinguishing GDM status (Area under the curve [AUC]=0.774), whereas the Ure/Cre ratio showed modest performance (AUC=0.614). In multivariate analysis, second-trimester Cre/BW and Urea/Cre ratios remained independently associated with GDM after adjustment for clinically relevant covariates. These results suggest a potential association; however, the discriminatory performance of the Cre/BW and Urea/Cre ratios should be regarded as exploratory rather than diagnostically definitive. Conclusions: Lower Cre/BW and higher Urea/Cre ratios were associated with GDM in this retrospective cohort. These findings suggest that simple renal-related biochemical ratios may reflect metabolic–renal adaptations in pregnancies complicated by GDM. However, given the modest diagnostic performance and retrospective design, these parameters should be considered exploratory indicators rather than standalone clinical tools. Further prospective studies are required to clarify their clinical relevance.